2018
DOI: 10.1093/mnras/sty1112
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of the stellar content of ultra-diffuse galaxies

Abstract: Understanding the peculiar properties of Ultra Diffuse Galaxies (UDGs) via spectroscopic analysis is a challenging task requiring very deep observations and exquisite data reduction. In this work we perform one of the most complete characterisations of the stellar component of UDGs to date using deep optical spectroscopic data from OSIRIS at GTC. We measure radial and rotation velocities, star formation histories (SFH) and mean population parameters, such as ages and metallicities, for a sample of five UDG can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 101 publications
10
84
0
Order By: Relevance
“…Only about a dozen higher surface brightness Coma UDGs have measured spectroscopic stellar population properties ( Ferré-Mateu et al (2018); Ruiz-Lara et al (2018); Gu et al (2018); Chilingarian et al (2019)). These studies generally found intermediate-to-old ages and low metallicities.…”
Section: Udg Stellar Massesmentioning
confidence: 99%
“…Only about a dozen higher surface brightness Coma UDGs have measured spectroscopic stellar population properties ( Ferré-Mateu et al (2018); Ruiz-Lara et al (2018); Gu et al (2018); Chilingarian et al (2019)). These studies generally found intermediate-to-old ages and low metallicities.…”
Section: Udg Stellar Massesmentioning
confidence: 99%
“…In Figure 8 we compare the luminosityweighted age distribution of galaxies in our sample to that of UDGs observed in the Coma (Gu et al 2018;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018) and Virgo (Pandya et al 2018) clus- Considering that we only have luminosityweighted ages, the results from the our analysis are expected to be biased toward the youngest populations within a galaxy. Therefore, a few different, non-exclusive scenarios can explain the additional fraction of UDGs with young ages.…”
Section: The Luminosity-weighted Ages Of Field Udgsmentioning
confidence: 99%
“…Prole et al 2019), are available for many UDGs but are of limited value in determining the properties of the stellar populations, while spectroscopy, which can provide the necessary information, is only available for a small number of galaxies (e.g. Martínez-Delgado et al 2016;Kadowaki et al 2017;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018;Gu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Ultra Diffuse Galaxies (UDGs) appear to be ubiquitous in groups and clusters (e.g., van Dokkum et al 2015a,b;Janowiecki et al 2015;Koda et al 2015;Muñoz et al 2015;Mihos et al 2015Mihos et al , 2017Merritt et al 2016;van der Burg et al 2016;Yagi et al 2016;Janssens et al 2017;Shi et al 2017) but are also observed in the field (e.g., Román & Trujillo 2017;Leisman et al 2017). Spectroscopic studies of a few cases indicate intermediate to old, metal poor stellar populations for UDGs in groups and clusters (Ferré-Mateu et al 2018;Gu et al 2018;Ruiz-Lara et al 2018) while the spectral energy distribution (SED) fitting of a field UDG points towards younger stellar populations in the field (Pandya et al 2018). Possible formation scenarii include UDGs being (i) failed Milky Way-like galaxies that lost their gas after forming their first stars (van Dokkum et al 2015a(van Dokkum et al ,b, 2016Yozin & Bekki 2015;Peng & Lim 2016;Lim et al 2018), possibly due to the denser environment in groups and clusters, (ii) the highspin tail of the dwarf galaxy population (Amorisco & Loeb 2016;Rong et al 2017;Shi et al 2017), (iii) tidal debris from mergers or tidally disrupted dwarfs (Beasley & Trujillo 2016;Greco et al 2018;Jiang et al 2018) or (iv) galaxies whose spatial extend is due to episodes of inflows and outflows from stellar feedback (Di Cintio et al 2017).…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%